Corak Tafsir Periode Pertengahan - Muhamad Erpian Maulana (Bayani, 2021)
The mid period is a golden period for the Islamic world, especially tafseer. In this period, apart from the separation of tafseer with hadith as a separate scientific study, it was also the time when knowledge outside of the two of them had entered the body of interpretation. The fact has a big influence on the interpretation of its status as a product of human thought, where each interpretation has its own orientation and group. This paper aims to examine the diversity of interpretations in the mediecal period. The author uses a qualitative research method with a historical-content analysis approach. In this study it was found that in the middle period there were at least five interpretive styles, namely: linguistic, fiqh, theological, mystical and philosophical.